The Analysis Meaning of Metallica Album “And Justice for All" - Tengku Khalifalah S; Ervina C M Simatupang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to explain the types of idioms and meanings contained in the album. This research uses a qualitative descriptive method. The data were taken from the album the theory used to analyze Longman (2003) “Idiom is a phrase which something different from the meanings of the separate words from which it formed”. The result of this result is irreguler: 2 (40%) regular: 3 (60%).  The idioms and meanings contained in this album, where idioms are sentences that cannot be concluded literally which indirectly these two points are related to each other.